Kawasan Kebisingan Bandar Udara Internasional Husein Sastranegara, Bandung, Provinsi Jawa Barat - Nissa Putri Ramadhan; Melati Ferianita Fachrul; Widyatmoko Widyatmoko (President University, 2019)
This research was conducted to determine the Husein Sastranegara International Airport Noise Area in Bandung with the Weighted Equivalent Continuous Perceived Noise Level (WECPNL) method. There are 12 measurement points determined based on the International Civil Aviation Organization (ICAO) at a distance of 650 m parallel to the runway, and 1000 m, 2000 m, 3000 m and 4000 m from the end of the runway. Noise intensity measurements using the Environment Meter CEM DT-8820, tripod and GPS. Data analysis was done in the study using the Weighted Equivalent Continuous Perceived Noise Level (WECPNL) method. Based on Government Regulation No. 40 of 2012 concerning the Development of Environmental Conservation in the Airport it is known that the location in the Noise Zone Level 1 is 70 £ WECPNL < 75, the Noise Zone Level 2 is 75 £ WECPNL < 80 and the Noise Zone Level 3 is WECPNL ³ 80. In the Noise Zone Level 3 there are school buildings, offices, parks and residential areas. At Noise Level 1 there are school buildings, parks and residential areas. The results of the study concluded that the highest WECPNL index value is on the runway 650 m WECPNL index value of 72,6, 1000 m distance of WECPNL index value of 68,7, 2000 m distance of WECPNL index value of 66,7, distance of 3000 m value the WECPNL index is 66,5 and the distance of 4000 m the value of the WECPNL index is 66,6. The WECPNL index results at Bandung Husein Sastranegara International Airport have a Level 3 Noise Zone and a Noise Level 1 Area which have school buildings and settlements that should not be all owed. Therefore, it is necessary to apply the concept of sound suppression in the form of planting trees and usage of building materials.